Perinatal outcomes of singletons following vitrification versus slow-freezing of embryos: a multicenter cohort study using propensity score analysis - Gu, Fang; Li, Shuzhen; Zheng, Lingyan; Gu, Jing; Li, Tingting; Du, Hongzi; Gao, Caifeng; Ding, Chenhui; Quan, Song; Zhou, Canquan; Li, Ping; Xu, Yanwen (Human reproduction (Oxford), 2019)
Is embryo vitrification associated with a higher risk of adverse perinatal outcomes than slow-freezing? Embryo vitrification was not associated with increased risks of adverse perinatal outcomes of pre-term birth (PTB), low birthweight (LBW), small for gestational age (SGA), large for gestational age (LGA) and macrosomia, as compared to slow-freezing. Vitrification is becoming a widely adopted technology for embryo cryopreservation with higher embryo survival rate and live birth rate than the slow-freezing technique. However, limited data are currently available on risks of adverse perinatal outcomes following vitrification as compared to that of slow-freezing. The impact of vitrification on perinatal outcomes remains further to be elucidated. Six large reproductive medical centers in Guangdong province, Southeast of China, took part in this multicenter retrospective cohort study. Cohorts of 3199 live born singletons after Day 3 frozen-thawed embryo transfer (FET) cycles with either vitrification or slow-freezing between January 2011 and December 2015 were included in the study. Each patient only contributed one cycle per cohort and vanishing twins were excluded. Propensity score (PS) matching was used to control for potential confounding factors. All live-born singletons following either a vitrified or a slow-frozen cleavage FET cycle during the period from 2011 to 2015 were analyzed. Perinatal outcomes of PTB, LBW, macrosomia, SGA and LGA were compared. The vitrified and slow-frozen cohorts were matched by propensity scores with a 1:1 ratio accounting for potential confounding factors associated with perinatal outcomes. These variables included baseline demographics (maternal age, BMI, education level, parity, type of infertility and cause of infertility), as well as IVF characteristics (insemination method, endometrial preparation protocol and embryo cryopreservation duration). A total of 2858 cases from vitrified embryo transfer (ET) and 341 babies from the slow-freezing group were included. After PS matching, 297 pairs of newborns were generated for comparison. The median gestational age was 39 weeks for both cohorts and the birthweights were comparable (3187.7 ± 502.1 g in the vitrified group vs. 3224.6 ± 483.6 in the slow-freezing group, P>0.05). There were no significant differences between the two groups on the incidence of PTB (5.4% vs. 7.7%), LBW (6.7% vs. 5.7%), macrosomia (5.7% vs. 6.1%), SGA (12.5% vs. 8.4%) and LGA (6.4% vs. 8.1%). Parallel logistic regression analysis indicated that vitrification was non-inferior to slow-freezing method in terms of the occurrence of PTB (OR, 0.68 [95% CI, 0.35, 1.31]), LBW (OR, 1.19[0.61-2.32]), macrosomia (OR, 0.94 [0.48-1.86]), SGA (1.55[0.91-2.64]) and LGA (0.78[0.42-1.45]), P>0.05. Sex-stratified PS matching models with multivariable regression analysis further confirmed that vitrification did not increase the risks of above-mentioned adverse perinatal outcomes in either the male or female infant cohort. Although the analysis was adjusted for a number of important confounders, the hospital dataset did not contain other potential confounders such as the medical history and obstetrics outcomes of women during pregnancy to allow adjustment. In addition, the current findings are only applicable to cleavage stage FET, but not pronuclei stage or blastocyst stage ET. Vitrified ET, in comparison with slow-frozen ET, was not associated with increased risks of adverse neonatal outcomes. With its superiority on live birth rates and non-inferiority on safety perinatal outcomes, transition from slow-freezing to the use of vitrification for embryo cryopreservation is reassuring. Nonetheless, future research is needed for the long-term effects of vitrification method on offspring's health outcomes. The study was funded by the National Key Research and Development Program (2016YFC100205), Guangzhou Science and Technology Project (201804020087), Guangdong Province Science and Technology Project (2016A020218008) and Guangdong Provincial Key Laboratory of Reproductive Medicine (2012A061400003). The authors have no conflicts of interest to declare.